The influence of gender in the direction of Spanish cooperative societies on profitability and indebtedness: an empirical analysis - Hernández Nicolás, Carmen María; Martín Ugedo, Juan Francisco; Minguez Vera, Antonio (REVESCO. Revista de Estudios Cooperativos, 2016)
In this paper the claim for the market for a new business management to ensure the presence of women in decision -making to respond to new social needs addressed. Thus, this paper analyzes the influence of gender diversity of the directors on the profitability and the level of debt for a sample of 5,199 Spanish cooperatives. Unlike capitalist societies, these organizations have a number of peculiarities in their government, and that the partners are themselves major time, agents and customers. The study focuses on the Spanish context, where there is an open debate on the importance of women's business management, as in other countries, driven by the proliferation of legislation on gender equality, being, in addition, Spain, the pioneer in having specific legislation on Social Economy. The results show that cooperatives with greater female representation in theirs Boards have higher profitability. On the other hand, those Boards with a higher percentage of women show a lower level of indebtedness.
Keywords: Gender; cooperatives; returns; debt.